Linguistic Features and Psychological States: The Case of Virginia Woolf - Du, Xiaowei (Frontiers in Psychology, 2022)
This study investigated the relation between psychological states and linguistic features with the case of Virginia Woolf. We analyzed the data from The Diary of Virginia Woolf (Bell, 1984) and Virginia Woolf: Biography (Bell, 1972) by automatic text analysis, stepwise multiple regression, and Pearson correlation. The results suggested that the significant linguistic features can jointly predict the psychological states of Virginia Woolf, including anger words, the absolutist word “everything”, and the total of first-person plural pronouns. Meanwhile, we developed an equation that can predict the psychological states of Virginia Woolf. In addition, text lengths affected the prediction of the psychological states of Virginia Woolf, but not the accuracy of the prediction. We discussed the findings and enumerated the limitations of this study at the end of the paper. The results not only complemented previous studies in understanding of the relation between language and psychological health, but also facilitated timely identification, intervention, and prevention of mental disorders.